THE EFFECT OF FILLER CONTENT ON MECHANICAL PROPERTIES OF POLYPROPYLENE/CLAY NANOCOMPOSITES - Rihayat, Teuku; Mustafa, Noor; Mustapha, Saari (Politeknik Negeri Lhokseumawe, 2007)
This study investigates the effect of filler content on mechanical properties for polypropylene. There are synthesis clay and un-synthesis clay used as filler content. Different ratio of clay was d in polypropylene to study which ratio have a better mechanical properties. The tensile test was carried out using INSTRON5565 and the maximum stress, strain, and modulus of elasticity observed. Results of the study showed that polypropylene/clay nanocomposite has a higher maximum stress compare to pure polypropylene and un-synthesis clay have a lowest. Besides that modulus of elasticity of specimen calculated and finds that it increased with increment filler content and strain did not affect by filler. The conclusion is synthesis clay filled into polypropylene will having a better material.Keywords: Nanocomposite, polypropylene, synthesis clay.